The Influence of Mood on Subordinates' Ability to Resist Coercive Pressure in Public Accounting1. (25th May 2015) - Johnson, Eric N.; Lowe, D. Jordan; Reckers, Philip M. J.
Abstract: This study reports on an experiment conducted to assess the influence of different affective mood states on auditors' ability to resist obedience pressure to commit or overlook unethical acts in six audit contexts. Obedience pressure from superiors to comply with unethical directives is of particular concern in public accounting, given the hierarchical structure of audit teams and the power imbalance in superior–subordinate relationships. One hundred and seventy audit seniors from two large international public accounting firms participated in an experiment. Three different moods were induced in participants through work‐related trigger events: one positive active mood state (arousal) and two negative passive mood states (fear and insignificance). These mood states were anticipated to influence auditors' expressed willingness to comply with their superiors' unethical directives as set forth in our ethical scenarios. Our results indicate that low levels of arousal and high levels of fear and insignificance influenced compliance intentions. Our results also indicate overall high levels of expressed willingness to comply with superiors' unethical directives. Implications of our findings for understanding the antecedents of unethical conduct within the accounting profession and for future research are discussed.